First you have to solve for one of the variables in terms of the other. Take one of the equations for example a+b=1000 and solve for a to get a=1000-b. Now you can substitute this expression into the other equation instead of a. 7a+15b=11504 becomes 7(1000-b)+15b=11504. Now we expand the parenthesis 7000-7b+15b. Combine like terms 7000+8b=11504. Subtract 7000 from both sides 8b=4504. Divide both sides by 8, b=563. Now you can substitute b into either of the original expressions and solve for a. It's best to use the easier one. a+563=11504. a=437. Hope this helps.